Reconstruction of Alzheimer’s Disease Cell Model In Vitro via Extracted Peripheral Blood Molecular Cells from a Sporadic Patient - Sijun Liu; Yuying Zhao; Xiaoying Su; Chengcheng Zhou; Peifen Yang; Qiusan Lin; Shijun Li; Hanxu Tan; Qi Wang; Changjun Wang; Qingguang Wu (Stem Cells International)
The establishment of human-induced pluripotent stem cell (iPSC) models from sporadic Alzheimer’s disease (sAD) patients is necessary and could potentially benefit research into disease etiology and therapeutic strategies. However, the development of sAD iPSC models is still limited due to the multifactorial nature of the disease. Here, we extracted peripheral blood mononuclear cells (PBMCs) from a patient with sAD and induced them into iPSC by introducing the Sendai virus expressing Oct3/4, Sox2, c-Myc, and Klf4, which were subsequently induced into neural cells to build the cell model of AD. Using alkaline phosphatase staining, immunofluorescence staining, karyotype analysis, reverse transcription-polymerase chain reaction (RT-PCR), and teratoma formation in vitro, we demonstrated that the iPSC derived from PMBCs (PBMC-iPSC) had a normal karyotype and potential to differentiate into three embryonic layers. Immunofluorescence staining and quantitative real-time polymerase chain reaction (qPCR) suggested that PBMC-iPSCs were successfully differentiated into neural cells. Detection of beta-amyloid protein oligomer (AβO), beta-amyloid protein 1-40 (Aβ 1-40), and beta-amyloid protein 1-42 (Aβ 1-42) indicated that the AD cell model was satisfactorily constructed in vitro. In conclusion, this study has successfully generated an AD cell model with pathological features of beta-amyloid peptide deposition using PBMC from a patient with sAD.